In-Vivo Effect of Andrographolide on Alveolar Bone Resorption Induced by Porphyromonas gingivalis and Its Relation with Antioxidant Enzymes. (17th September 2013) - Al Batran, Rami; Al-Bayaty, Fouad H.; Al-Obaidi, Mazen M. Jamil
Abstract : Alveolar bone resorption is one of the most important facts in denture construction. Porphyromonas gingivalis ( Pg ) causes alveolar bone resorption, and morphologic measurements are the most frequent methods to identify bone resorption in periodontal studies. This study has aimed at evaluating the effect of Andrographolide (AND) on alveolar bone resorption in rats induced by Pg . 24 healthy male Sprague Dawley rats were divided into four groups as follows: normal control group and three experimental groups challenged orally with Pg ATCC 33277 five times a week supplemented with 20 mg/kg and 10 mg/kg of AND for twelve weeks. Alveolar bones of the left and right sides of the mandible were assessed by a morphometric method. The bone level, that is, the distance from the alveolar bone crest to cementumenamel junction (CEJ), was measured using 6.1 : 1 zoom stereomicroscope and software. AND reduced the effect of Pg on alveolar bone resorption and decreased the serum levels of Hexanoyl-Lysine (HEL); furthermore the reduced glutathione/oxidised glutathione (GSH/GSSG) ratio in AND treated groups (10 and 20 mg/kg) significantly increased when compared with the Pg group ( P < 0.05 ) . We can conclude that AND suppresses alveolar bone resorption caused by Pg in rats.